Security Competence as an Integral Part of Competence-Based Learning Approach: Russian and European Experience - Goncharova, Yana (2021)
Since the end of the 20th century, educational standards have been changing, and many countries have switched from a traditional approach to a competence-based one. Despite the numerous works on the issue, there is still no standardized definition of competencies and their components. The study of the competencies, including new digital competencies, is neces-sary because education within the framework of the competence-based approach helps to reduce the gap between theory and practice, which makes it possible to train specialists ready to work in a new digital era, where one of the main tasks is the formation of the digital economy. The digital economy implies the development and creation of digital, high-tech products within the country. The ability to safely operate digital products is reflected in security competence, which is important not only in professional activities but also when using the internet, computer programs, and so on, for personal purposes. In this article, we will analyze different approaches to the concept of security competence within the prism of competence-based learning in Russia and Western countries, including European and American experiences.